2005
DOI: 10.1210/jc.2005-0285
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Persistent or Recurrent Disease of Papillary Thyroid Carcinoma with Neck Lymph Node Metastases and/or Tumor Extension beyond the Thyroid Capsule at Initial Diagnosis

Abstract: We highlight an excellent survival rate and suggest risk classifications of persistent and recurrent disease based on the numbers of LN metastases and ECE-LN, LN metastases location, tumor size, and thyroglobulin level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
391
7
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 541 publications
(428 citation statements)
references
References 29 publications
19
391
7
11
Order By: Relevance
“…For this reason, although the size of the LN and metastatic foci was not available for our patients, the fact that US was negative ensures the absence of LNM > 3 cm and makes LNM > 1.5 cm highly unlikely. Although defined as an exclusion criterion of the present study, macroscopic extranodal invasion is uncommon in the case of small LNM (16,20,38) and not present in large numbers (15,16,38). In fact, extranodal invasion was observed in only 7/466 patients with LNM < 3 cm and up to 5 positive LN in a previous series (16) and in only 1/87 patients with negative US and up to 5 positive LN in the present study (data not shown).…”
Section: Evolution Of Patients With Persistent Disease or Tumor Recurcontrasting
confidence: 38%
See 3 more Smart Citations
“…For this reason, although the size of the LN and metastatic foci was not available for our patients, the fact that US was negative ensures the absence of LNM > 3 cm and makes LNM > 1.5 cm highly unlikely. Although defined as an exclusion criterion of the present study, macroscopic extranodal invasion is uncommon in the case of small LNM (16,20,38) and not present in large numbers (15,16,38). In fact, extranodal invasion was observed in only 7/466 patients with LNM < 3 cm and up to 5 positive LN in a previous series (16) and in only 1/87 patients with negative US and up to 5 positive LN in the present study (data not shown).…”
Section: Evolution Of Patients With Persistent Disease or Tumor Recurcontrasting
confidence: 38%
“…There was no case of death due to the disease. (9)(10)(11)(12)(13)(14), the presence of more than 5 positive LN (11,(15)(16)(17)(18), metastases ≥ 3 cm (11,16,19), and extranodal extension (15,16,(18)(19)(20)(21) are also associated with a poor prognosis (4,5,7,22). In these cases, there is little controversy about the need for a more aggressive initial approach.…”
Section: Evolution Of Patients With Persistent Disease or Tumor Recurmentioning
confidence: 99%
See 2 more Smart Citations
“…Putting in mind that in PTC, lymph node metastases have been shown to increase the risk of locoregional tumor recurrence (Hay et al, 1999;Leboulleux et al, 2005;Cheema et al, 2006;Ito and Miyauchi, 2007) and that approximately 5% of patients with PTC were identified as having superior mediastinal metastases (Roh et al, 2008;Machens and Dralle, 2009) with concerns that metastatic lymph node involvement is nothing more than indolent microscopic disease without clinical significance and that the sensitivity of ultrasound and CT range between only 50 and 70 % Mulla, (2012), and on the other hand Wang et al, 2013 advocated the unnecessary CND in some patients with incidental PTC postoperatively and that the impact of positive regional lymph nodes on survival has been controversial (Steinmuller et al, 2000), we performed a prophylactic CND including level VI and VII from the same collar neck incision (Block et al, 1972). Yu et al, 2012 recommended the "wait and see" strategy for clinically negative level V in low risk PTC patients and stated that it would still achieve good survival results.…”
Section: Discussionmentioning
confidence: 99%